2023
DOI: 10.5267/j.ijdns.2023.3.012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social media marketing on purchase intention: The mediating role of brand trust and image

Abstract: This research examines how social media marketing affects brand image, brand trust, and purchase intention in the context of beauty centers in Jordan. The study presents a model that outlines the influence of social media marketing strategies on customer behavior. To support the proposed model, a quantitative method was employed to collect data through online surveys. The sample consisted of 374 respondents selected through non-probability convenience sampling techniques. The data was analyzed using PLS-SEM me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Third, there are research results that explain the significant positive relationship that emerges between social network variables and purchase intention. This finding strengthens the results of previous research conducted by Salhab et al (2023) which found that social networks had a significant positive effect on purchase intention. Social networks play a vital role in enhancing an individual's intention to buy a product.…”
Section: Discussionsupporting
confidence: 91%
“…Third, there are research results that explain the significant positive relationship that emerges between social network variables and purchase intention. This finding strengthens the results of previous research conducted by Salhab et al (2023) which found that social networks had a significant positive effect on purchase intention. Social networks play a vital role in enhancing an individual's intention to buy a product.…”
Section: Discussionsupporting
confidence: 91%
“…So, it is concluded that digital marketing is not significantly affecting purchase intention through brand trust. The results of this study are similar the results of (Salhab et al 2023) and (Putri and Anggarawati 2022) which states that a great marketing strategy is not enough to build trust between consumer and the brand since client won't feel like to trust by only aware about the brand and consumer won't feel any purchase intention. The brand trust variable obtained an R squared value of 0.351, which proves that the independent variables, namely brand ambassadors, brand image and digital marketing, can explain the brand trust variable by 35.1%, while the remaining 64.9% can only be explained by various other factors not included in the model.…”
Section: Hypothesis 10: Digital Marketing Has a Significant Effect On...supporting
confidence: 87%
“…The marketing component known as the Marketing Mix demonstrates a noteworthy association with Intention to Purchase (Hossain et al, 2020). that the Intention to Purchase is significantly impacted by the Marketing Mix (Salhab et al, 2023). H2: There is a positive influence of Marketing Mix on ITP.…”
Section: Literature Reviewmentioning
confidence: 98%